Risk of atrial fibrillation in hypertrophic cardiomyopathy: a clustering analysis based on the French registry on hypertrophic cardiomyopathy (REMY). (8th February 2021) - Hourqueig, M; Bouzille, G; Mirabel, M; Huttin, O; Damy, T; Labombarda, F; Eicher, J-C; Charron, P; Habib, G; Reant, P; Hagege, A; Donal, E
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): CHU Rennes, Inserm, LTSI – UMR 1099, F-35000 Rennes, France Assistance Publique-Hôpitaux de Paris-Centre Université de Paris, University of Paris onbehalf: REMY register Paroxysmal or chronic atrial fibrillation (AF) is frequent in hypertrophic cardiomyopathy (HCM), (20%-25% of patients), and is often considered as an important disease turning point. The aim of this study is to determine HCM-phenogroups with different risk of AF-occurrence at 5-year. We applied the Bayesian method to differentiate phenogroups of patients with different risks of AF across a French hospital registry of adult HCM(REMY). Data were prospectively recorded on 5 years follow-up. 1431 HCM patients were recruited, including 1275 analyzed. The population included 412 women. AF-occurred in 167 (11.6%) patients. 3 phenogroups were defined according to their common characteristics. Patients at the highest risk were more often female, with more frequent comorbidities, greatest anteroposterior LA diameter, diastolic dysfunction, outflow-tract obstruction or mitral valve abnormality, and presented higher sPAP or right ventricular dysfunction. These also had a higher risk of all-cause hospitalizations and death. Based on a clustering analysis, 3 phenogroups of HCM according to the risk of AF occurrence can be identified. It can indicate which patients should be more monitored.